Stereotactic radiosurgery and immunotherapy in melanoma brain metastases: Patterns of care and treatment outcomes. Issue 2 (August 2018) - Gabani, Prashant; Fischer-Valuck, Benjamin W.; Johanns, Tanner M.; Hernandez-Aya, Leonel F.; Keller, Jesse W.; Rich, Keith M.; Kim, Albert H.; Dunn, Gavin P.; Robinson, Clifford G.; Chicoine, Michael R.; Huang, Jiayi; Abraham, Christopher D.
Abstract: Purpose: Preclinical studies have suggested that radiation therapy (RT) enhances antitumor immune response and can act synergistically when administered with immunotherapy. However, this effect in melanoma brain metastasis is not well studied. We aim to explore the clinical effect of combining RT and immunotherapy in patients with melanoma brain metastasis (MBM). Materials and methods: Patients with MBM between 2011 and 2013 were obtained from the National Cancer Database. Patients who did not have identifiable sites of metastasis and who did not receive RT for the treatment of their MBM were excluded. Patients were separated into cohorts that received immunotherapy versus patients who did not. Univariable and multivariable analyses were performed using Cox model to determine predictors of OS. Kaplan–Meier method was used to compare OS. Univariable and multivariable analyses using logistic regression model were used to determine the factors predictive for the use of immunotherapy. Propensity score analysis was used to account for differences in baseline patient characteristics between the RT and RT + immunotherapy groups. Significance was defined as a P value ≤ 0.05. Results: A total of 1104 patients were identified: 912 received RT alone and 192 received RT plus immunotherapy. The median follow-up time was 6.4 (0.1–56.8) months. Patients with extracranial disease (OR 1.603, 95% CI 1.146–2.243, P = 0.006), and patients receiving SRS (OR 1.955, 95% CI 1.410–2.711, P < 0.001) as compared to WBRT, had a higher likelihood of being treated with immunotherapy. The utilization of immunotherapy had nearly doubled between 2011 and 2013 (12.9–22.8%). On multivariable analysis, factors associated with superior OS were younger age, lower medical comorbidities, lack of extracranial disease, and treatment with immunotherapy and SRS. The median OS was 11.1 (8.9–13.4) months in RT plus immunotherapy vs. 6.2 (5.6–6.8) months in RT alone ( P < 0.001), which remained significant after propensity score matching. Conclusions: An increase in trend for the use of immunotherapy was noted, however, an overwhelming majority of the patients with this disease are still treated without immunotherapy. Addition of immunotherapy to RT is associated with improved OS in MBM. Given the selection biases that are inherent in this analysis, prospective trials investigating the combination of RT, especially SRS and immunotherapy are warranted.